8 - Subjectivity in Servitude: The Servant and Indigenous Family Arrangement in Written Igbo Drama: par Frances Ν. Chukwukere - Chukwukere, Frances N. (Africa Development, 2005)
Membership into the African family may be on the basis of natural (birth) or social (marriage, adoption, apprenticeship, etc) selection. The present paper examines the roles of eleven servants in eight plays written in Igbo language by six authors. The work considers the perception of the servant by other charac ters in these works of art, the way in which each of these servants perceives him/ herself, and the roles of the servant in the development of the entire fictional enterprise. Finally, the theory of subjectivity: the conscious and unconscious thoughts and emotions that largely account for the relationship between the in dividual and the society, is used in the present work to explain the authors' presentations of the servants in these dramatic works of fiction.